The Effect of Entrepreneurship Education on Entrepreneurial Intention by Entrepreneurial Self-Efficacy - Deliana, Marlina; Simanjorang, Feronica (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
Entrepreneurship education is considered an important factor in preparing individuals to become entrepreneurs by providing the necessary knowledge and skills. This study aims to analyze how entrepreneurship education affects entrepreneurial self-confidence which then impacts the intention to start a business. Data was collected using quantitative research to test the relationship between variables through purposive sampling technique with a sample of 45 respondents, namely students who have taken entrepreneurship courses at the University of North Sumatra, Faculty of Social and Political Sciences, Business Administration Study Program. The results showed that entrepreneurship education has a significant positive influence on entrepreneurial self-efficacy, which in turn contributes to increasing entrepreneurial intention. This finding confirms the importance of entrepreneurship education programs in shaping students' entrepreneurial mentality and attitude, as well as providing a strong foundation for them to face the challenges of the business world. Therefore, entrepreneurship education needs to be strengthened to better prepare individuals for their entrepreneurial journey